Molecular sexing of tigers, Panthera tigris - McEwing, R.; Ouitavon, K.; Rovie-Ryan, J. J.; M., Wulansari; Sitam, F. T.; Ogden, R. (Springer Nature, 2011)
We report the development of a fast and reliable PCR-based method for sex identification of tiger DNA designed to be incorporated into fluorescent short tandem repeat (STR) profiling. A single primer pair, consisting of a fluorescently-labelled forward primer and an unlabelled reverse primer, is used to co-amplify homologous fragments of a zinc finger (ZF) protein intron which exhibits size polymorphism between the X and Y chromosomes. The ZFX and ZFY amplicons differ in size by 12 bp and can thus be differentiated by capillary electrophoresis.